2020
DOI: 10.2147/copd.s271844
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effectiveness of Steroid Therapy on Pneumonic Chronic Obstructive Pulmonary Disease Exacerbation: A Multicenter, Retrospective Cohort Study</p>

Abstract: To date, no consensus exists on the effects of systemic steroid use on pneumonic chronic obstructive pulmonary disease (COPD) exacerbation owing to trial design issues in previous trials involving these conditions. This multicenter study aimed to evaluate more precisely the effectiveness of the use of systemic steroids in treating pneumonic COPD exacerbation in a larger sample by adjusting for confounding factors. Patients and Methods: This multicenter, retrospective, observational study was conducted across f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

6
0

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
(25 reference statements)
0
12
1
Order By: Relevance
“…25 However, in daily practice, pulmonary function test results might be missing, especially from the patients' rst visit. 17 Our study selected easily accessible variables that physicians can use in various clinical settings. Second, in our dataset, the eosinophil count was missing in 44.7% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 However, in daily practice, pulmonary function test results might be missing, especially from the patients' rst visit. 17 Our study selected easily accessible variables that physicians can use in various clinical settings. Second, in our dataset, the eosinophil count was missing in 44.7% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…To select the patients with pneumonic COPD-AE, we used a validated selection algorithm based on the 10th revision of the International Statistical Classi cation of Diseases and Related Health Problems (ICD-10) in another study. 17 Speci cally, we used the following criteria: (1) the admission precipitating the diagnosis of pneumonia (ICD-10 codes: J12, J13, J14, J15, J16, J18, J69, and P23) with comorbidity of COPD or COPD-AE (ICD-10 codes: J44.1 and J44.9) and ( 2) the admission precipitating diagnosis of COPD exacerbation (ICD-10 code; J44.1) with comorbidity of pneumonia (ICD-10 codes: J12, J13, J14, J15, J18, J69, and P23). We excluded the following other causes of respiratory failure: heart failure (ICD-10 code; I50), pneumothorax (ICD-10 code: J93), asthma exacerbation (ICD-10 code: J45), obstructive pneumonia (ICD-10 code: J188).…”
Section: Study Participantsmentioning
confidence: 99%
“…Pneumonic COPD exacerbation is diagnosed when the criteria for both pneumonia and COPD exacerbation are met [ 4 , 12 , 13 ]. To select patients with pneumonic COPD exacerbation, we used the validated algorithm based on the 10th revision of the International Classification of Diseases and Related Health Problems (supplementary eFigure S1 ) [ 4 ]. First, patients aged ≥40 years who had both pneumonia and COPD exacerbation were selected.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with COPD often experience acute worsening of baseline symptoms, and with coexisting consolidation (pneumonic COPD exacerbation) on chest imaging, mortality is increased compared to non-pneumonic COPD exacerbation [ 2 ]. A previous study suggested that pneumonic COPD exacerbation might have a different inflammation profile from non-pneumonic COPD exacerbation [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patient selection was based on a validated algorithm for selecting patients with pneumonic COPD exacerbation [9]. The algorithm was based on the 10th revision of the International Classi cation of Diseases and Related Health Problems.…”
Section: Methodsmentioning
confidence: 99%